Next generation sequencing reveals plants consumed by the vulnerable ebony langur (Trachypithecus auratus) in a fragmented mountain forest - Puguh Karyanto; Adifa Risa Bagasta; IKE NURJUITA NAYASILANA; SHUKOR MD NOR; Sri Suci Utami Atmoko; Ari Susilowati; SUNARTO SUNARTO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Karyanto P, Bagasta AR, Nayasilana IN, Nor SMD, Atmoko SSU, Susilowati A, Sunarto 2022. Next generation sequencing reveals plants consumed by the vulnerable ebony langur (Trachypithecus auratus) in a fragmented mountain forest. Biodiversitas 23: 4759-4769. Many mountain forests on Java Island have suffered from forest degradation, fragmentation, and alien species invasion that cause a significant change in vegetation structure. This changing floristic structure may affect the foraging substrate of the foliage eater ebony langur, Trachypithecus auratus. Hence, ascertaining the plants eaten by the langur may contribute significantly to informing important ecological data about its foraging adaptation and conservation. We analyzed six fecal samples of the langur from three forest sites in Mount Merbabu National Park, Indonesia. This research used the plant mini barcode to sequence the ribulose-biphosphate carboxylase gene (rbcl) in the mitochondrial DNA of the plants eaten by the langur using the Next Generation Sequencing. We compare the NGS results to floristic reference data from a vegetation survey preceding the fecal analysis. The NGS found 238 OTUs that belong to 32 taxa. Most of the langur’s diet belongs to the lower crop community. The study’s results suggest that the ebony langur’s dietary composition shows an adaptation to the new floristic composition. However, since the habitat is continuously degraded, the stakeholders must perform appropriate home-building-based habitat management practices to conserve this vulnerable species.